2007
DOI: 10.1007/s11552-007-9030-x
|View full text |Cite
|
Sign up to set email alerts
|

Baseline Predictors of Pain and Disability One Year following Extra-Articular Distal Radius Fractures

Abstract: Distal radius fractures are common injuries; however, identifying which factors are responsible for predicting outcomes remains an area of controversy. The purpose of this study was to define factors predictive of patient-reported pain and disability at 1 year in a prospective cohort of extra-articular distal radius fractures (n=222). Data were collected at the initial visit and after 3, 6, and 12 months. The primary outcome was the 1-year patientrated wrist evaluation (PRWE) score. The effect of baseline pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
85
2
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 69 publications
(92 citation statements)
references
References 13 publications
3
85
2
2
Order By: Relevance
“…12,19,21 Some studies have postulated that suboptimal radiographic outcomes may be a concern but may not always result in chronic pain or disability. 3,11,16 This implies that some individuals can still expect favorable outcomes despite poor union of the DRF.…”
Section: T T Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…12,19,21 Some studies have postulated that suboptimal radiographic outcomes may be a concern but may not always result in chronic pain or disability. 3,11,16 This implies that some individuals can still expect favorable outcomes despite poor union of the DRF.…”
Section: T T Resultsmentioning
confidence: 99%
“…Injury compensation and educational level were found to be highly predictive of chronic pain and MSKD 12,19 and led to difficulty in returning to work 21 following DRF. Our analysis was limited due to unavailability of data related to injury compensation.…”
Section: Discussionmentioning
confidence: 98%
“…The authors reported that the baseline characteristics of the patients and the injuries in extra-articular distal radial fractures had a minor role in predicting the patients likely to develop pain and disability after 1 year [12].…”
Section: Discussionmentioning
confidence: 99%
“…7,8 Non-injury factors such as age, injury compensation, education, and comorbidities also affect patient-rated outcome. 9,10 This study aimed to identify factors that affect functional outcome one year after distal radial fracture treatment.…”
mentioning
confidence: 99%